Is the Creativity of First-Year Students in Stoichiometry Learning Affected by Their Chemistry Scholastic Ability? - Asih, Findiyani Ernawati; Azizah, Utiya; Rachmadiarti, Fida; Sukarmin, Sukarmin (Journal of Innovation in Educational and Cultural Research, 2026)
This study aims to examine the correlation between scholastic ability in chemistry and creativity in stoichiometry learning among first-year students. Chemistry scholastic ability is naturally integrated among first-year students who demonstrate their reasoning skills in the field of chemistry, which may influence students' creativity in their chemistry learning. This quantitative research used a correlational design to examine two variables without providing an intervention. The research results showed a significant correlation between scholastic ability in chemistry and creativity, but were inconsistent across the two creativity measures (verbal assessment of creativity [VAC] and figural assessment of creativity [FAC]). Chemistry scholastic ability had a significant correlation with VAC. The first-year students identified had moderate-level reasoning ability, as evidenced by their difficulties transforming stoichiometry knowledge at the microscopic-symbolic level. Students' reasoning abilities encouraged the emergence of an original idea for molecular modeling using environmentally friendly materials (VAC). Even though they did not achieve high-level reasoning ability, they succeeded in creating a mind map (FAC) on stoichiometry by supporting digital literacy. Reasoning ability can foster creativity as one of the 21st-century skills, enabling students to directly contribute to preserving the environment by using molecular modeling materials. They also solve daily-life problems more easily by applying stoichiometry knowledge visualized in a mind map.